أثر استخدام استراتيجية الصف المقلوب في تعلم برمجة الحاسب بلغة الفيجوال بيسك والاتجاه نحو تعلم برمجة الحاسب - الفيفى، يوسف يحى; الحسن، رياض عبدالرحمن محمد (جامعة البحرين - مركز النشر العلمي, 2018)
The purpose of this study was to examine the effect of the Flipped Classroom Strategy on learning computer programing in Visual Basic Studio and attitudes toward learning computer programming among Saudi secondary students. The study adopted an experimental methodology with a quasi-experimental design, to examine the effect of the flipped classroom on achievement in computer programing in Visual Basic, and students' attitudes toward learning programing. The study sample consisted of 58 2nd level high school students. The sample was divided into two groups, experimental and control. An achievement test on computer programing knowledge and practical skills, and a questionnaire to explore students' attitudes toward learning programing were used to collect the study data. Findings showed that there were statistically significant mean differences between the experimental and the control groups in the academic achievement in programming knowledge and skills in favor for the experimental group. Moreover, the study found statistically significant mean differences between the experimental and the control groups in their attitudes toward learning programing in favor of the experimental group.
هدفت هذه الدراسة إلى التعرف على أثر استخدام استراتيجية الصف المقلوب على تعلم برمجة الحاسب بلغة الفيجوال بيسك والاتجاه نحو تعلم البرمجة. وقد اتبعت الدراسة منهج البحث التجريبي بتصميم شبه تجريبي للتعرف على أثر المتغير المستقل (استخدام الصف المقلوب) على المتغيرين التابعين (التحصيل في البرمجة بلغة الفيجوال بيسك والاتجاه نحو تعلم البرمجة). وقد تألفت عينة الدراسة من ثمانية وخمسين طالبا من طلاب المستوى الثاني في المرحلة الثانوية بنظام المقررات بمدينة الرياض، مقسمين إلى مجموعتين إحداهما تجريبية والأخرى ضابطة، وتمثلت أداة الدراسة في اختبار تحصيلي في المعارف المتعلقة بالبرمجة، واختبار عملي يشمل مهارات البرمجة العملية، بالإضافة إلى استبانة لقياس الاتجاه نحو تعلم البرمجة. وقد أظهرت النتائج وجود فروق ذات دلالة إحصائية عند مستوى (0.05) في التحصيل بين المجموعة التجريبية والمجموعة الضابطة في المعارف المتعلقة بالبرمجة لصالح المجموعة التجريبية، كما أظهرت النتائج وجود فروق ذات دلالة إحصائية عند مستوى (0.05) في التحصيل الدراسي بين المجموعتين في مهارات البرمجة العملية بلغة الفيجوال بيسك ستوديو Visual Basic Studio، وذلك لصالح المجموعة التجريبية، كما أظهرت النتائج وجود فروق ذات دلالة إحصائية عند مستوى (0.05) بين المجموعة الضابطة في اتجاه الطلاب نحو تعلم البرمجة وذلك لصالح المجموعة التجريبية.
Keywords: الاستراتيجيات التربوية -- استراتيجية الصف المقلوب -- البرمجة الإلكترونية -- لغة الفيجوال بيسك -- التحصيل الدراسى